Advances in Construction and Development Proceedings of CDLC 2020 - Vatin, Nikolai I.; Tamrazyan, Ashot G.; Plotnikov, Alexey N.; Leonovich, Sergei N.; Pakrastins, Leonids; Rakhmonzoda, Ahmadjon; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book contains the materials of the Conference "Construction and Development: Life Cycle-2020" (CDLC-2020), held at Chuvash State University, Russia. The content of this volume is devoted to improving methods for calculating building structures, strengthening them and assessing their suitability for use, monitoring buildings, improving building technologies, geotechnics, energy efficiency of building envelopes and energy systems, introducing new structures and materials, and economic assessment of construction. It also consists of test data for load-bearing building structures. This volume will prove to be a valuable resource for those in academia and industry. .
Architecture and Urbanism -- Calculation and design of building structures -- Reliability, durability and design of the reconstruction of buildings and structures -- Monitoring of buildings and structures -- Geotechnics, soil mechanics and foundations for construction and renovation of buildings -- Technology, Project Planning, Construction Management and Economics of buildings construction and renovation.
Keywords: Buildings -- Design and construction; Buildings -- Repair and reconstruction; Buildings -- Maintenance; Engineering geology; Building Construction and Design; Building Repair and Maintenance; Geoengineering; Building -- Mathematics -- Congresses; Civil engineering -- Mathematics -- Congresses